Knowledge, Attitude and Associated Factors Toward Ethiopian Abortion Law Among Reproductive Age Women in Bule Hora Town, Southern Oromia, Ethiopia, 2022 - Zelalem Jabessa Wayessa; Balela Areri Boneya; Elias Amaje Hadona (Health Services Research & Managerial Epidemiology, 2023)
Objectives A woman's health and wellbeing are impacted by illegal abortion since improper procedures can lead to consequences like extreme bleeding, infection, and damage to the reproductive organs and low awareness and attitude toward abortion law is one of the public health problems in Ethiopia. This study aimed to assess the knowledge, and attitude, and identify the effect of short birth interval and wealth index on the abortion law among reproductive-age women in Bule Hora town, Southern Oromia, Ethiopia. Methods A community-based cross-sectional study design was conducted from June 20 to July 20, 2022. A systematic random sampling technique was carried out to select 402 reproductive-age women. Data was collected by using a structured questionnaire with face-to-face interviews after the tools were pretested. The data was cleaned, coded, and entered into Epidata 3.1 and exported to STATA 14 for analysis. The model goodness of fit was checked using the Hosmer-Lemeshow test. Statistical significance is declared at P  < .05 and a 95% confidence interval. Results The study revealed that 153 (38%) of respondents had good knowledge and 192 (47%) had a favorable attitude toward the Ethiopian abortion law, with a 100% response rate. Women's educational status, having information regarding the criteria of legal abortion services, and short birth intervals as a reason for induced abortion were significantly associated with knowledge. On the other hand, women who attended secondary education and above, have information regarding the criteria of legal abortion services, wealth index middle/average and richer, using the contraceptive method, and short birth interval as a reason for induced abortion were predictors of attitude toward Ethiopian abortion law. Conclusion This study shows that knowledge and attitude toward Ethiopian abortion law was not sufficient. So focusing on awareness creation and health education strategies by mobilization of the community to minimize the knowledge and attitude gap is essential.